Effects of perceived origin on anti-migrant sentiments and acts of socially induced hatred in Bulgaria - Spasova, Lyuba D. (Sociološki pregled, 2021)
The paper studies the effects of perceived immigrants’ origin on anti-immigrant sentiments in the Bulgarian society by focusing on social distance and some aspects of socially induced hatred towards immigrants. Spread and approval of hate speech and hate violence against immigrants and variations associated to the perceived different background and origin are analyzed. With respect to social distancing, two clusters are differentiated – “distant” and “close” on basis of origin and the differences between them are not only in the degree of acceptance, but also in the ranking of preferred roles. With respect to act of socially induced hatred results are more ambiguous. Origin has a substantial role on the spread of hate speech, but this is not the case with the spread or (perceived) involvement of different groups in violence. Inclination to intervene and stop violence differs according to the origin of victims and perpetrators and further studies are needed to identify determinants.
Keywords: social distance; anti-immigrant sentiments; hate speech; hate violence